Hypermedia-Integrated Print Textbooks: Bridging The Traditional and Digital Learning Gap - Daeli, Deomesta Oscar; Siregar, Eveline; Cecep Kustandi (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Digital learning offers flexibility to its users, but its dependence on internet access is a barrier, especially in remote areas that still lack internet facilities. This research aims to identify student learning problems and their causes, as well as identify alternative solutions that can be used to overcome student learning problems. This research is a descriptive study using observation, interview and questionnaire methods. The main problems found were limited practicum facilities and limited textbooks. The analysis shows that there are studies on digital learning and textbooks, but few studies discuss the integration of hypermedia in printed textbooks as an alternative. This research offers an innovation in the form of a printed textbook model integrated with hypermedia that presents interactive elements such as videos, animations, simulations and digital links that can be accessed when students are within the reach of the internet. The printed textbook model integrated with hypermedia is expected to enrich students’ learning experience. The conclusion of this research is that the incorporation of hypermedia in printed textbooks can be an effective alternative to bridge between traditional textbook-based learning and digital technology-based learning, and opens up new potential in the development of interactive learning materials in the future.